Do Modern Technologies Work for the Rural ICT and Rural Credit Institutions in India? - Fu, X; Polzin, C (SLPTMD (Department of International Development, University of Oxford), 2008)
This paper explores the impact of various forms and levels of ICT on the performance of rural cooperative banks using recent survey data from India. Findings from the research suggest that modern information technology serves to enhance both the efficiency and profitability of the rural credit institutions. Efficiency was significantly enhanced by the usage of moderate technology at the lower organisational level, e.g. stand-alone computers at the branch level, mobile phone usage at PACS (Primary Agricultural Credit Society) and field level. However, profitability appears to be associated with more advanced and sophisticated usage of information technology at branch or lower organisational level. Complementarities in human capital, training in IT skills of the bank staff, absorptive capacity of the customers and community, are of crucial importance for the efficiency of rural cooperative banks. Evidence from this study also suggests that using investment in ICT as a measure of the usage and advancement level of information technology may not reveal the full story of the impact of ICT on the efficiency of organizations.